When special populations intersect with drug–drug interactions: Application of physiologically‐based pharmacokinetic modeling in pregnant populations. (26th April 2021) - Sychterz, Caroline; Galetin, Aleksandra; Taskar, Kunal S.
Abstract: Pregnancy results in significant physiological changes that vary across trimesters and into the postpartum period, and may result in altered disposition of endogenous substances and drug pharmacokinetics. Pregnancy represents a unique special population where physiologically‐based pharmacokinetic modeling (PBPK) is well suited to mechanistically explore pharmacokinetics and dosing paradigms without subjecting pregnant women or their fetuses to extensive clinical studies. A critical review of applications of pregnancy PBPK models (pPBPK) was conducted to understand its current status for prediction of drug exposure in pregnant populations and to identify areas of further expansion. Evaluation of existing pPBPK modeling efforts highlighted improved understanding of cytochrome P450 (CYP)‐mediated changes during pregnancy and identified knowledge gaps for non‐CYP enzymes and the physiological changes of the postpartum period. Examples of the application of pPBPK beyond simple dose regimen recommendations are limited, particularly for prediction of drug–drug interactions (DDI) or differences between genotypes for polymorphic drug metabolizing enzymes. A raltegravir pPBPK model implementing UGT1A1 induction during the second and third trimesters of pregnancy was developed in the current work and verified against clinical data. Subsequently, the model was used to explore UGT1A1‐related DDI risk with atazanavir and rifampicin along with the effect of enzyme genotype on raltegravir apparent clearance. Simulations of pregnancy‐related induction of UGT1A1 either exacerbated UGT1A1 induction by rifampicin or negated atazanavir UGT1A1 inhibition. This example illustrated the advantages of pPBPK modeling for mechanistic evaluation of complex interplays of pregnancy‐ and drug‐related effects in support of model‐informed approaches in drug development. Abstract : Pregnancy represents a unique special population where physiologically‐based pharmacokinetic modeling (PBPK) is well suited to mechanistically explore pharmacokinetics and dosing paradigms without subjecting pregnant women or their fetuses to extensive clinical studies. Evaluation of existing pregnancy PBPK (pPBPK) modeling efforts identified knowledge gaps for non‐CYP enzymes and the physiological changes of the postpartum period, and limited application of pPBPK beyond simple dose regimen recommendations, particularly for prediction of drug–drug interactions (DDI) or differences between genotypes for polymorphic drug metabolizing enzymes. In addition, a raltegravir pPBPK model implementing UGT1A1 induction during the second and third trimesters of pregnancy was developed in the current work to explore UGT1A1‐related DDI risk with atazanavir and rifampicin along with the effect of enzyme genotype on raltegravir apparent clearance.